Next-Generation Sequencing in Early Diagnosis of Dent Disease 1: Two Case Reports - Wen, Min; Shen, Tian; Wang, Ying; Li, Yongzhen; Shi, Xiaoliu; Dang, Xiqiang (Frontiers in Medicine, 2018)
Dent disease 1 is a rare X-linked recessive inherited disease, caused by pathogenic variants in the chloride voltage-gated channel 5 (CLCN5) gene. Dent disease 1 is characterized by low molecular weight (LMW) proteinuria, hypercalciuria, nephrocalcinosis, and chronic kidney disease. Infants may manifest only asymptomatic LMW proteinuria, which increases the difficulty of early diagnosis. We describe two male infants presenting only with nephrotic-range LMW proteinuria observed on examination using urine protein electrophoresis. Hereditary renal tubular diseases were highly suspected based on early onset age and LMW proteinuria. Thus, next-generation sequencing was performed and pathogenic mutations in CLCN5 were identified in both patients. After obtaining written informed consent, a diagnosis of Dent disease 1 was made. The two patients developed hypercalciuria during late follow-up, which verified the diagnosis. These two cases highlight the importance of next-generation sequencing in the early diagnosis of Dent disease 1 with only LMW proteinuria.